The Relationship of The Mandibular Canal to The Roots of Impacted Third Molars- The Root Factor: A Panoramic Radiographic Study - Bali, Harleen; Yadav, Deepak; Adhikari, Khushbu; Mahanta, Swagat Kumar; Tripathi, Rupam; Sapkota, Binam (Journal of Lumbini Medical College, 2020)
Introduction: Third molar extractions are one of the most common reasons of injury to mandibular nerve and postoperative complications. Pre-operative assessment of pending doom is a must. In order to study the relations between change in Inferior Alveolar Canal (IAC) and Type, Class, and Level of impaction with radiographic root change of impacted third mandibular molar, we designed a study to assess the relationship of the mandibular canal to the roots of impacted third molar in reference to changes in roots and factors affecting it. Methods: This was a retrospective cross-sectional study wherein the panoramic radiographic records of subjects with impacted third molar were assessed for change in root and its correlation with change in IAC, Type, Class and Level of impacted mandibular third molar. Results: Roots of impacted third molar when in contact with IAC presented most often in our study subjects with the Darkening of roots in both sides {right side (16.79%) and left side (11.29%)} and both genders {males (right-14.29%, left-8.75%) and females (right-19.39%, left-13.94%)}. They were statistically significantly associated with interruption of white line of IAC, vertically impacted third molars and Pell and Gregory Class II, Level A of impaction. Conclusion: There is a need to properly identify radiographic risk predictor signs to avoid any surprises at the time of extraction and post operation complications following it.